Information Technology Innovation With Tricky Card Game For Prevention And Handling Hypertension and Diabetes Mellitus In An Effort to Improve the Quality Of Healthy Life Of the Elderly in Tilongkabila Public Health Center - Adam, Lusiane; Pangalo, Paulus; Ischak, Wenny Ino; Usman, Lisdiyanti; Buheli, Kartin (Journal of Health and Nutrition Research, 2025)
Hypertension and diabetes mellitus (DM) are degenerative diseases that are often suffered by the elderly. Efforts made in the form of information technology innovation application based on whatsapp bot with tricky card game. The purpose of this study Knowing the design and implementation of information technology innovation whatsapp bot gopos health with tricky card game for the prevention and treatment of hypertension and diabetes mellitus to improve the quality of healthy life of the elderly at the Tilongkabila Community Health Center. The method used in this study is a mixed method with the type of research used is sequential transformation (sequential transformative strategy). where researchers design information technology innovation with a qualitative approach then the results of implementation and testing using a quantitative approach. The quantitative component measured in the form of a questionnaire sheet MO SF - 12 using a paired t test statistical test to test the effectiveness of a treatment and compare the average pre-test value and the average post-test value. The results of this study state that elderly people with hypertension and diabetes mellitus who have measured their quality of healthy life through the MO SF-12 questionnaire obtained statistical test results stating that the hypothesis Ha is accepted and H0 is rejected (P<0.05), namely that there is an influence of the application of information technology innovation for the prevention and treatment of hypertension and diabetes mellitus in an effort to improve the quality of healthy life of the elderly